Development and characterization of cell models harbouring mtDNA deletions for in vitro study of Pearson syndrome - Carmen Hernández-Ainsa; Ester López-Gallardo; María Concepción García-Jiménez; Francisco José Climent-Alcalá; Carmen Rodríguez-Vigil; Marta García Fernández de Villalta; Rafael Artuch; Julio Montoya; Eduardo Ruiz-Pesini; Sonia Emperador (The Company of Biologists, 2022)
Pearson syndrome is a rare multisystem disease caused by single large-scale mitochondrial DNA deletions (SLSMDs). The syndrome presents early in infancy and is mainly characterised by refractory sideroblastic anaemia. Prognosis is poor and treatment is supportive, thus the development of new models for the study of Pearson syndrome and new therapy strategies is essential. In this work, we report three different cell models carrying an SLMSD: fibroblasts, transmitochondrial cybrids and induced pluripotent stem cells (iPSCs). All studied models exhibited an aberrant mitochondrial ultrastructure and defective oxidative phosphorylation system function, showing a decrease in different parameters, such as mitochondrial ATP, respiratory complex IV activity and quantity or oxygen consumption. Despite this, iPSCs harbouring 'common deletion' were able to differentiate into three germ layers. Additionally, cybrid clones only showed mitochondrial dysfunction when heteroplasmy level reached 70%. Some differences observed among models may depend on their metabolic profile; therefore, we consider that these three models are useful for the in vitro study of Pearson syndrome, as well as for testing new specific therapies. This article has an associated First Person interview with the first author of the paper.